Fluid Balance, Hydration, and Athletic Performance - Meyer, Favia; Szygula, Zbigniew; Wilk, Boguslaw (Taylor & Francis, 2015)
Fluid Balance, Hydration, and Athletic Performance presents a comprehensive review of aspects relating to body fluid balance, rehydration, sport, and physical exercise. The content is scientifically supported, practical, and suitably written for a range of audiences, including academics (professors and students) and sports and health professionals (coaches, physical educators, nutritionists, and physicians), as well as athletes and individuals involved in physical activities. Compared to other books previously published in this area, this book does not limit body hydration issues to the average or elite adult athlete. Rather, it addresses aspects relevant to a range of individuals of different ages (adolescents and master athletes) competing in various sports. In recognition of the growing number of individuals with specific medical conditions who have been exercising more and even participating in competitive sports, separate chapters on prevalent diseases or medical conditions associated with risks of body fluid homeostasis also are presented. To achieve such a complete and qualified publication, the book is written by top experts and professionals experienced in their respective research areas. It presents the basics of fluid balance and provides updates on controversial fluid intake-related issues such as hyponatremia, optimal recovery, intermittent sports, and perceptual responses.